1998
DOI: 10.20506/rst.17.3.1136
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of dermatophilus congolensis infection in camels (Camelus dromedarius) from the Butana region in Eastern Sudan

Abstract: Natural Dermatophilus congoíensis infection of camels has been reported in Kenya in semi-arid areas. Research is being conducted to discover how widespread the condition is in neighbouring countries with similar eco-climatic conditions. Severe skin infections of camels from the Butana region of Eastern Sudan were examined. The infections were first found in two herds of adult camels, of which 50%-75% of the animals were affected. In the other thirteen herds examined, camel calves were more likely to be infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…congolensis infection is reported as one of the conditions that impede camel production in the Kenya, Sudan, and Saudi Arabia (Gitao et al 1998a). In Saudi Arabia, mixed infection involving D. congolensis and Microsporum gypseum have been found in 48 camels which had discrete circumscribed lesions (Gitao et al 1998b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…congolensis infection is reported as one of the conditions that impede camel production in the Kenya, Sudan, and Saudi Arabia (Gitao et al 1998a). In Saudi Arabia, mixed infection involving D. congolensis and Microsporum gypseum have been found in 48 camels which had discrete circumscribed lesions (Gitao et al 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…More than 200,000 dromedary camels are living in the arid and semiarid deserts of Iran (Rahbari and Bazargani 1995;Mowlavi et al 1997). In camels, dermatophilosis has been reported in Kenya, Sudan, and Saudi Arabia (Gitao et al 1998a(Gitao et al , b, 1990Gitao 1992), but has not been previously reported in Iran. Therefore, the present study describes the prevalence, pathogenesis, and gross and histopathologic lesions of this disease in the camels of the central part of Iran.…”
Section: Introductionmentioning
confidence: 96%
“…Dermatophilus congolensis causes exudative dermatitis in multiple species and is typically associated with tick and biting fly-transmission, although it can also be spread by contact [ 156 , 157 , 158 , 159 ]. Prevalence levels were similar in Kenya to Sudan and Iran, at between 12 and 30%, and were significantly higher during the wet season [ 53 , 160 , 161 ]. This may indicate an increased risk as camel production moves into areas with higher rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Camel Dermatophillosis has been reported in Kenya, Sudan and Saudi Arabia. In Sudan the outbreaks was in the Butana region, The fatality rates ranged from 0% in Saudi Arabia to 30% in Sudan, mixed infection involving Dermatophilus congolensis and Microsporum gypseum were founded [7] . Tick control in infected animals and environment is indicated to minimize the risk of Dermatophillosis [8] in study was carried out at Qas sim Region, Central of Saudi Arabia, to study dermatophytosis in a private farm of dromedary camels.…”
Section: Introductionmentioning
confidence: 99%